Bevacizumab-Irinotecan combination in the treatment of glioma. Issue 2 (12th March 2012) - Alcobia, A.; Leandro, A.; Costa, G.; Domingos, S.
Abstract : Background: Patients with recurrent malignant gliomas, such as glioblastoma multiform and anaplastic astrocytoma, have a poor prognosis. Repeat surgery may not be feasible, because of tumour infiltration, and additional irradiation has limited control on further tumour growth and would potentiate neurological toxicity. Treatment options are limited. The association of an angiogenesis inhibitor with a classical cytotoxic -bevacizumab plus irinotecan – is one of the options used by the neuro-oncologists. Purpose: Evaluate the effectiveness of combination bevacizumab and irinotecan in recurrent malignant gliomas. Materials and methods: Retrospective analyse of patients with gliomas treated with bevacizumab/irinotecan. Data source: medical records and patients prescription from the cytostatic unit in pharmacy department. The following variables were analysed: sex, age at diagnosis, diagnosis, previous treatment received, number of cycles and dose. Disease progression was evaluated by MRI. Results: This study included 16 patients (7 females, 9 males) with a mean age at diagnosis of 45, 75±9, 75 years (range 29-60). The principal diagnosis was glioblastoma multiform (68, 7%). Bevacizumab/Irinotecan was used in second-line treatment in 9 patients (56, 2%) and in third-line setting in 7 patients (43, 8%). Fifteen patients did radiation therapy with concurrent Temozolomide (TMZ) before Bevacizumab/Irinotecan, and all patients had undergone prior surgical resection. The mean number of cycles of bevacizumab/Irinotecan was 7, 9±5, 5 (1-16). Disease progression, was observed in 12 patients (75%) and 4 are still in treatment. Considering the patients who already stopped treatment, the calculated time to disease progression, based on the duration of bevacizumab/irinotecan treatment, was 22, 4 weeks. (Time to disease progression described in the literature: 23, 0 weeks). Conclusions: Preliminary results with Bevacizuman/Irinotecan in the treatment of patients with high grade gliomas are similar the results observed in the literature and encouraging in poor prognosis disease in malignant glioma.